DER VERGLEICH VON TERMINOLOGIEN, FACHTEXTEN UND FACHSPRACHEN AUS. METHODISCHER SICHT - Reiner Arntz (Revista de Lingüística y Lenguas Aplicadas)
The methods for comparing terminologies, technical texts and languages for special purposes are of interest from a theoretical, practical and pedagogical point of view. Particularly in the field of jurisprudence, considerable structural differences exist, both on the terminological level as well as on the text level. For the comparison of terminologies, the onomasiological method has proven to be particularly suitable. For comparing texts, various analytic methods have been developed, which can be combined very flexibly. With this as a basis, the description and the comparison of languages for special purposes form the link between the terminologies, the technical texts and technical communication.